Improving Overall Equipment Effectiveness Using Lean Six Sigma In Lube Blending Plant- A Case Study - Tukiran, Mohd Azizi (2020)
Overall Equipment Effectiveness (OEE) is a key indicator to measure operation performance and it has been introduced in Total Productive Maintenance (TPM) whichfocused towards zero breakdown, zero defect and zero incident. Since then, OEE has been evolved to wider application from measuring only single machine effectiveness to measuring overall global operation effectiveness. Therefore, to stay competitive in current turbulent and ch.allenging business environment, OEE improvement is very crucial with the aim to achieve world class manufacturing (WCM) standard. In this case study, it aims to improve OEE in one of the filling lines in Melaka Lube Blending Plant (MLBP) located in Tangga Batu, Melaka .. In addition, this case study was focused on reducing of planned and unplanned downtime of MLBP Bottle Line 3 (BL3). To achieve that aim, integration of lean manufacturing tools and techniques with six sigma methodology was used. Define, Measure, Analyse, Improve, and Control (DMAIC) cycle was a framework and lean manufacturing were used as tools and techniques to conduct the improvement activities. In Define, and Measure phase, OEE loss factor has been identified and measured through collecting quantitative and qualitative data. These data were obtained from primary and secondary source. To find the root causes and potential causes of the problem, collected and measured data were analysed in Analyse phase by using cause and effect diagram (CED), and failure mode and effect analysis (FMEA). To reduce downtimes, single minute exchange die (SMED) was used to reduce changeover process time (planned downtime). While autonomous maintenance (AM) was executed to reduce machine downtime (unplanned downtime). Both improvement activities were carryout in Improve phase. Last phase of this DMAIC cycle is Control phase. Standards works was developed to sustain the improvement activities. In addition, current OEE dashboard was used to control and monitoring OEE performance trend. Hence, by doing that, it helps to identify another improvement activity to further improve the OEE. At the end of this case study, OEE result was re-evaluated and the result was compared with the OEE result before improvement. Hence, OEE was improved from 48.8% to 66.5%.